Kata Tanya Mana dalam Dialek Pulau Pinang dalam Program Minimalis (Jurnal Bahasa, 2012)
This article discusses the question form of mana in the Penang dialect of Malay using Minimalist approach. The data analysed in this article were taken from a field study carried out in the state of Penang. The data were obtained from recording respondents' conversations in the Penang dialect. Two research methods were employed namely library method and field method. The library method was used to collect information related to the question form and the field method to obtain data in the research area. The research area covered all districts within the state of Penang. The resulting data were analysed using the Minimalist Programme. The in-situ or moved question forms are linked to a feature of the question form of mana itself and also an OP feature that prevents its movement. As a result, this analysis concludes that mana in the Penang dialect does not behave as in-situ but it does move.Keywords: question form, mana, Minimalist Programme, Penang dialect